PENGARUH VARIASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KUE KERING TIARA KOTA BENGKULU - Mardiansyah, Lefi; Ekowati, Sri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of product variation and product quality on purchasing decisions of Tiara Cookies in the city of Bengkulu. This type of research is a type of quantitative descriptive research. The sampling method uses a non probability technique, namely accidental sampling. The number of respondents in this study were 120 respondents. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, Determination Coefficient Analysis, and Partial Test (t test), Simultaneous Test (f test). The results of the study show that partially the Product Variable Variable has a positive effect on the Purchase Decision Variable, H1 is accepted and Product Quality has a positive effect on the Purchase Decision Variable, H2 is accepted. While the f Test of Product Variation (X1) and Product Quality (X2) has a positive influence on Purchase Decision (Y) Tiara Cookies Bengkulu City, so H3 is accepted. Product Variation and Product Quality together have a positive effect on the Purchase Decision of Tiara Cookies, Bengkulu City. Keywords: Product Variation, Product Quality and Purchase Decision